2016
DOI: 10.1111/aec.12475
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses of native and exotic grasses in a Neotropical savanna predict impacts of global change on invasion spread

Abstract: Communities subject to stress, including those with low invasibility, may be dominated by exotic generalist species. African grasses are aggressive invasive species in Neotropical savannas, where their response to abiotic stress remains unknown. We assessed the role of waterlogging and canopy closure on the presence, abundance and reproductive tillering of African and native grasses in a Neotropical savanna in southeastern Brazil. We obtained abundance and reproductive tillering data of exotic (Melinis minutif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Exotic grass cover, in turn, decreased linearly over time and was estimated to disappear from secondary savannas within 36 years. This is because the C4 grasses present at the study sites (U. decumbens and U. humidicola) are shade intolerant (Klink & Joly, 1989;Xavier, Leite, & da Silva-Matos, 2016), and the regenerating systems were estimated to exhibit forest canopy by the end of this period.…”
Section: Can Abandoned Pastures Approximate the Attributes Of Refermentioning
confidence: 99%
“…Exotic grass cover, in turn, decreased linearly over time and was estimated to disappear from secondary savannas within 36 years. This is because the C4 grasses present at the study sites (U. decumbens and U. humidicola) are shade intolerant (Klink & Joly, 1989;Xavier, Leite, & da Silva-Matos, 2016), and the regenerating systems were estimated to exhibit forest canopy by the end of this period.…”
Section: Can Abandoned Pastures Approximate the Attributes Of Refermentioning
confidence: 99%
“…In seasonally dry ecosystems, high water tables may even favour the occurrence of herbaceous species with poor tolerance to water deficit, as it may increase the moisture at the superficial soil layer by capillary action (Moore 1939). In effect, there is no annual period of water deficit in most of our study sites subjected to seasonal waterlogging (Xavier et al 2017). Therefore, we hypothesize that conditions associated with high water tables support specific herbaceous species, and competitive ability is expected to be important for their persistence (Grime 1988).…”
Section: Herbaceous Communitiesmentioning
confidence: 90%
“…Although we initially aimed to sample an equal the number of sites within each of these three savanna categories, we found that woody cover varies widely within each savanna category (Leite et al 2018). Likewise, we found that grassland types initially categorized based on visual differences in their flooding regime were in effect distributed along a hydrological gradient, including distinct annual periods of soil waterlogging and standing water (Xavier et al 2017). Considering these limitations on identifying a priori physiognomies or vegetation types at our study site and our aim of assessing community responses to water table depth, our study focus on assessing diversity patterns of woody and plant communities occurring along a continuum of woody cover and hydrological regimes.…”
Section: Study Sitementioning
confidence: 93%
See 1 more Smart Citation
“…Por outro lado, no arranjo obtido pelas relações entre variáveis expressas por unidade de massa seca foliar, foi observada uma tendência de aumento no desempenho fotoquímico de invasoras em presença de dossel, enquanto que em nativas a tendência é novamente inversa.A partir dos resultados, sugere-se que nativas e invasoras diferiram quanto ao microclima luminoso ideal para o desempenho máximo de uso da luz, e que a estrutura foliar estaria associada com essa diferença. Estudos em fisionomias de cerrado mostram que a abundância de invasoras pode estar positivamente correlacionada com a disponibilidade de luz(Pivello et al, 1999b), e que o grau de fechamento do dossel pode afetar diferentemente o desempenho reprodutiva de gramíneas nativas e invasoras(Xavier et al, 2016). Ainda que este estudo não tenha incluído altos graus de fechamento de dossel como fonte de variação, as implicações dos padrões de desempenho de uso da luz na aptidão de nativas e invasoras devem ser consideradas.…”
unclassified